Function and Meaning of Oral Literature of The Besemah Tribes of Muaradua Kisam, South Oku (Literary Anthropological Study) - Yesvica Apryanti; Siti Rukiyah; Darwin Effendi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The aim of this research is to determine the function and. The meaning of guritan oral literature in the Besemah tribe community in Muaradua Kisam. South Oku is reviewed and studied by literary anthropology, especially aspects of religious language and customs. This research uses the method, descriptive qualitative analysis. Data collection techniques in this research user observation techniques, interview techniques, SLC (Simak Libat Cakap) listening techniques, recording techniques and not-taking techniques. Data sources in this research include aspects and primary data, namely data in the form of videos of oral literature from the people of Besemah Muaradua Kisam Oku South in traditional events. Apart from that, other sources of data are secondary data, namely data sourced from books and journals relate to the problems in the research. Based on research conducted, there are 47 poems which are included in language aspect, 27 poems which are included in the religious aspect, and 13 poems which are included in the customs aspect. Keywords: Besemah Society, Guritan Oral Literature, Literary Anthropology